Reagan and Thatcher's special relationship : Latin America and Anglo-American relations - Treharne, Sally-Ann (Edinburgh : Edinburgh University Press, 2015)
A unique insight into one of the most controversial political relationships in recent history. The Falklands War, the US invasion of Grenada, the Anglo-Guatemalan dispute over Belize and the US involvement in Nicaragua - in the 1980s, these crises threatened to overwhelm a renewal in US-UK relations. Sally-Ann Treharne vividly portrays the role of personal diplomacy between US President Ronald Reagan and UK Prime Minister Margaret Thatcher in overcoming obstacles to Anglo-American relations emanating from the turbulent Latin American region in the final years of the Cold War. Drawing on recently declassified documents and elite interviews with key protagonists that reveal candid recollections, she highlights the pivotal moments in Reagan and Thatcher's shared history from a new vantage point.
Title from publisher's bibliographic system (viewed on 30 Oct 2017).
Keywords: Reagan, Ronald; Thatcher, Margaret; Falkland Islands War, 1982.; United States -- Foreign relations -- Great Britain; Great Britain -- Foreign relations -- United States; United States -- Foreign relations -- 1981-1989.; Great Britain -- Foreign relations -- 1979-1997.; Grenada -- History -- American Invasion, 1983.